Implementation Of The SAFE4C Program To Build A Safe And Child-Friendly Environment: A Case Study In Five Villages Of Malang Regency - YUSRONI, AHMAD (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
This study analyzes the implementation of the SAFE4C Program in building a safe and child-friendly environment in five villages of Malang Regency (Madiredo, Pandanmulyo, Ngijo, Petungsewu, Pandanlandung) using a qualitative multiple case study approach. Based on the LPA East Java–UNICEF Partnership Agreement (PCA2022278, June 6, 2022), the program targets the establishment of Village Child Forums (FAD), DARA Task Forces, and supporting infrastructure. Data were collected through participatory observation (12 coordination meetings, 5 village assistances), in-depth interviews (n=25), and document analysis (2022 decrees, LPA reports 2023–2025, SIMFONI PPA). Thematic analysis revealed 100% institutional outputs (decrees, 50 trained facilitators, 50 FAD members), an 18% increase in case reporting (SIMFONI PPA, 2025), and 65% victim resilience via MHPSS. Challenges include age miscommunication in FAD (Madiredo), gender/hamlet imbalance (Ngijo), Perdes delay (20%), and low facilitator activity (42%). 2026 development plans include FAD reorganization, infrastructure integration, and Perdes enactment. This research fills the empirical gap in SAFE4C village-level implementation and recommends replication in 70 East Java villages with annual monitoring for post-UNICEF sustainability.